Alfalfa hay levels in limit-fed, high-energy, growing diets for beef steers - Sean P. Montgomery; J.J. Sindt; T.B. Farran; H.J. LaBrune; R.D. Hunter; James J. Higgins; T.A. Nutsch; R.A. Stock; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2000)
One hundred sixty-four crossbred beef steers were used in a 102-day growing study to determine optimum levels of alfalfa hay in limit-fed, high-energy, growing diets. Diets contained steam-flaked corn and 40% Sweet Bran® brand wet corn gluten feed (dry matter basis) with 0, 10, or 20% ground alfalfa hay. A fourth diet containing steam-flaked corn (no Sweet Bran) and 20% ground alfalfa hay was used as a control. Average daily gains and feed efficiencies in the growing phase were greater (P.40) among diets during the finishing phase.
Keywords: Cattlemen' s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Wet corn gluten feed; Sweet Bran®; Roughage; Limit feeding